The Teaching of Arabic Studies in Nigerian Universities and the Underrepresentation of Females in the Field - Yusuf, Tajudeen (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This paper investigates the teaching of Arabic studies in Nigerian universities, focusing on the challenges and factors contributing to the underrepresentation of female students and educators. Arabic holds significant religious, cultural, and historical value in Nigeria; however, female participation in the field remains limited. Through an in-depth exploration of societal, cultural, and institutional barriers, this study identifies major obstacles that discourage women from enrolling in and pursuing careers in Arabic studies. Key barriers include restrictive gender norms, minimal female faculty representation, and perceptions of limited career prospects, which collectively reinforce gender disparities in the field. The study also reviews current initiatives that promote gender equity in Arabic studies and proposes actionable strategies, such as curriculum reform, community outreach, and mentorship programs, to enhance female enrollment and retention. By addressing these socio-cultural and institutional challenges, the paper seeks to encourage policies and reforms that foster inclusivity, support female advancement, and improve the overall quality of Arabic education in Nigeria. The study concludes with recommendations aimed at achieving gender equity and strengthening the academic landscape of Arabic studies in Nigerian universities, thereby contributing to a more balanced and inclusive academic field.